A Review of Friction Dissipative Beam-to-Column Connections for the Seismic Design of MRFs - Piero Colajanni; Muhammad Ahmed; Salvatore Pagnotta; Pietro Orlando (Applied Sciences, 2024)
The use of friction-based beam-to-column connections (BCCs) for earthquake-resistant moment-resistant frames (MRFs), aimed at eliminating damage to beam end sections due to the development of plastic hinges, has been prevalent since the early 1980s. Different technical solutions have been proposed for steel structures, and some have been designed for timber structures, while a few recent studies concern friction joints employed in reinforced concrete structures. Research aimed at characterizing the behavior of joints has focused on the evaluation of the tribological properties of the friction materials, coefficient of friction, shape and stability of the hysteresis cycles, influence of the temperature, speed of load application, effects of the application method, stability of preload, the influence of seismic excitation characteristics on the structural response, statistical characterization of amplitude, and frequency of the slip excursion during seismic excitation. Studies aimed at identifying the design parameters capable of optimizing performance have focused attention mainly on the slip threshold, device stiffness, and deformation capacity. This review compiles the main and most recent solutions developed for MRFs. Furthermore, the pros and cons for each solution are highlighted, focusing on the dissipative capacity, shape, and stability of hysteresis loops. In addition, the common issues affecting all friction connections, namely the characteristics of friction shims and the role of bolt preload, are discussed. Based on the above considerations, guidelines can be outlined that can be used to help to choose the most appropriate solutions for BCCs for MRFs.